Transfer of Labour Time on the World Market: Religious Sanctions and Economic Results - Jørgen Sandemose (Religions, 2012)
This paper investigates the extent to which a term like “globalization”, especially in its sense of implying the existence of a system, or of dominant features favouring development towards some system, is adaptable to a theory of a world economy which is to take due notice of the structure of the exchange value of commodities on the world market. A leading idea is that religious outlooks, in the way they were conceptualized by Karl Marx, have a strong bearing upon the difference in labour intensities in countries contributing to the world market, and thereby upon the differences in international values and prices. These differences are expressed in a scale-based, rigid structure on the world market itself—a structure which gives us the fundamental reason why certain specific countries or areas may get steadily poorer in relative terms, while others may constantly get relatively richer through the same mechanism. Consequently, when (as it is done here) religion is taken to express the quintessence of the cultural level of societies, it can be said that the comparative study of religions gives us a key to the understanding of crucial economic differences between nations. The differences in question are primarily those prevailing between capitalist societies on the one hand, and non-capitalist, or what is here called patrimonial societies, on the other.